Propagação de jamboleiro [Syzygium cumini (L.) Skeels] - Silva, Marciéli (2017)
Syzygium cumini (L.) Skeels is an exotic species native to Asia, but its is cultivated a lot of countries, including Brazil. Although there are few commercial plantations of this fruit tree, it has many possibilities of commercialization, market of fresh fruits to processing such as jams, liqueurs, vinegar, jellies, pies and sweets. The objective of the work was to test propagation techniques in order to obtain an appropriate protocol for this species. The experiments were carried out in the Laboratory of Plant Physiology and Unit of Teaching and Research Nursery, at Federal Technological University of Paraná - Câmpus Dois Vizinhos. The storage of S. cumini seeds was during 0, 30, 60, 90, 120, 150, 180, 210, 240, 270, 300, 330, 360 days. The storage followed by hydrocondicionamento in temperature of 25 °C during 0, 12, 24, 36, 48, 60, 72, 84, 96, 108, 120, 132, 144 and 156 hours. The germination percentage, germination speed index and average germination time after 60 days were evaluated, according each time. In the mini-cuttings, indole-butyric acid (IBA) concentrations (0, 2000, 3000, 4000 mg.L-1) and type of cuttings (apical, middle and basal) were tested. In the cutting experiment, IBA concentrations (0, 5000, 10000 mg.L-1) and Benzylaminopurine (BAP) concentrations (0, 250 and 500 mgL-1) were evaluated. In the second cutting experiment, conditioning techniques (control, ringing and etiolation), conditioning time (40, 60, 80 and 100 days) and IBA concentrations (0, 2000, 4000 mg.L-1) were tested. In the air layering we used types of coating (withoutcolor plastic, aluminum paper and black plastic), IBA concentrations (0, 2000 and 4000 mg.L-1), presence or not of cotton and seasons of the year. In order to evaluate the percentage of rooting, root number, length of the three largest roots, and presence of callus by cuttingFor the S. cumini it was recommended the storage followed by hydrocondicionamento for up to 156 hours, the use of middle and basal minicuttings without the IBA application. The air layering was the technique propagation that it was possible higher rooting values.